Yu-Gi-Oh! R. Volume 3, The perfect duel - Itō, Akira (Takahashi, Kazuki, 1961- Yu-gi-oh! R, 2010)
Yugi and his friends battle their way through an army of enemies at Kaibacorp headquarters! Jonouchi faces Reiko, a chess-themed duelist, while Yugi fights Depres in the cosmic duel field of outer space. Can Yugi's earthly cards defeat Depres's deck of alien monsters? Plus a bonus story about Yugi and his grandpa!